Breaking of physical dormancy and evaluation of environmental factors on seed germination of field dodder parasite (Cuscuta Campestris) - ahmad zare; Zeinab Porameri (علوم و فناوری بذر ایران)
In order to knowledge the dormancy and seed germination of field dodder in response to environmental factors (sulfuric acid (physical dormancy), light, temperature, salinity and drought stress) four separate experiments were conducted at agricultural scientists and natural recourses university of Khuzestan. Treatments of sulfuric acid (96%) immersion (0, 10, 20, 30, 60, 90 and 120 m exposure to sulfuric acid), temperature (5, 10, 15, 20, 25, 30, 35, 40, 45°C). Light (light/dark and darkness), salinity (0, 50, 100, 150, 200, 250, 300, 350, 400 and 400 mM) and drought stress (0, -0.2,-0.4, -0.6, -0.8, -1 and -1.2 MPa) were considered. Seed immersion for 30 m increased germination up to 100% while by increasing of seed immersion in sulfuric acid to 120 minutes, germination decreased to 60%. Seed germination were at 10°C (53%), 20 (88%), 25 (100%), 30 (100%), 35 (100%) and 40°C (42%). Germination of field dodder wasn’t dependent on light. The salinity required to 50% inhibition for traits germination percentage, germination index and germination rate were predicted 154.89, 139.71 and 119.11mM respectively. From the results of drought stress indicated that for 50% inhibition of germination percentage, germination index and germination rate (logistic equation) were predicted -0.57, -0.43 and 0.52 MPa respectively.